Ruthenium indenylidene complexes bearing N-alkyl/N-mesityl-substituted N-heterocyclic carbene ligands - Yu Baoyi; Fatma B. Hamad; Bert Sels; Kristof Van Hecke; Verpoort F. V. K. Frensis Valter Kornelius (2015, 2015)
Title screen